(untitled) (Journal of Applied Science and Engineering A, 2023)
In this research, climate change over the last 22 years (2000-2022) in Durvoljin, Ugramal and Erdenekhairkhan Sum areas of Zavkhan province was determined and desertification status was assessed using satellite data. In this research, the soil-adjusted vegetation index (SAVI) was calculated among the vegetation indi-ces. When SAVI is calculated using data from the red and NIR channels of the MODIS satellite data, SAVI values vary between -0.4 and +0.5 as a result of im-age processing. The spatial heterogeneity of the land surface of the study area was mapped by SAVI values from -0.4 to +0.02 for water, +0.02 to +0.08 for gravel and rock, +0.08 to +0.11 for sand, +0.11 to +0.16 for sparse soil, +0.16 from - to +0.23 with sparse vegetation, and between +0.23 and +0.5 with good vegetation in 6 categories. As a result of the study, SAVI proved to be more suitable for determining soil types in desert and semi-desert areas.